Identification of Novel Mutations in Spatacsin and Apolipoprotein B Genes in a Patient with Spastic Paraplegia and Hypobetalipoproteinemia - Leema Reddy Peddareddygari; Raji P. Grewal (Case Reports in Genetics)
Complicated hereditary spastic paraplegia (HSP) presents with complex neurological and nonneurological manifestations. We report a patient with autosomal recessive (AR) HSP in whom laboratory investigations revealed hypobetalipoproteinemia raising the possibility of a shared pathophysiology of these clinical features. A lipid profile of his parents disclosed a normal maternal lipid profile. However, the paternal lipid profile was similar to that of the patient suggesting autosomal dominant transmission of this trait. Whole exome sequence analysis was performed and novel mutations were detected in both the SPG11 and the APOB genes. Genetic testing of the parents showed that both APOB variants were inherited from the father while the SPG11 variants were inherited one from each parent. Our results indicate that, in this patient, the hypobetalipoproteinemia and spastic paraplegia are unrelated resulting from mutations in two independent genes. This clinical study provides support for the use of whole exome sequencing as a diagnostic tool for identification of mutations in conditions with complex presentations.